Microbiota-Immune Interaction in the Pathogenesis of Gut-Derived Infection - Wang, Chenyang; Li, Qiurong; Ren, Jianan (Frontiers in Immunology, 2019)
Gut-derived infection is among the most common complications in patients who underwent severe trauma, serious burn, major surgery, hemorrhagic shock and severe acute pancreatitis. It might cause sepsis and multiple organ dysfunction syndromes which are regarded as a leading cause of mortality in these cases. It has been widely recognized that gut-derived infection is mainly caused by the translocation of intestinal bacteria or endotoxins, resulting from the disruption of intestinal barrier. The intestinal barrier is mainly composed of epithelial barrier, intestinal microbial barrier and mucosal immune barrier. In the last decades, the studies regarding to the pathogenesis of bacterial translocation mainly focused on intestinal epithelial tight junction and intestinal permeability. Yet, little information is available on the roles of intestinal microbiota and mucosal immune barrier in the development of gut-derived infection. Recently, advances of next-generation DNA sequencing techniques and its utilization has revolutionized the gut microecology, leading to novel views into the composition of the intestinal microbiota and its connection with diseases. Also, the findings provide knowledge of how the gut microbiota collaborates with mucosal immune cells and epithelial cells to be involved in the formation of bacterial translocation. Here, we reviewed the recent progress in the researches of intestinal barrier injury and gut-derived infection, mainly through the perspectives of the dysbiosis of intestinal microbiota and its interaction with intestinal epithelial and mucosal immune barrier. The data might have important implication to better understand the mechanism underlying intestinal bacterial translocation, contributing us to develop new strategies for prevention and treatment of gut-derived infection.